We think you are located in United States. Is this correct?

Solving cubic equations

5.5 Solving cubic equations (EMCGX)

Now that we know how to factorise cubic polynomials, it is also easy to solve cubic equations of the form \(a{x}^{3}+b{x}^{2}+cx+d=0\).

Worked example 13: Solving cubic equations

Solve: \(6{x}^{3}-5{x}^{2}-17x+6 = 0\)

Find one factor using the factor theorem

Let \(f(x) = 6{x}^{3}-5{x}^{2}-17x+6\)

Try

\(f\left(1\right)=6{\left(1\right)}^{3}-5{\left(1\right)}^{2}-17\left(1\right)+6=6-5-17+6=-10\)

Therefore \(\left(x-1\right)\) is not a factor.

Try

\(f\left(2\right)=6{\left(2\right)}^{3}-5{\left(2\right)}^{2}-17\left(2\right)+6=48-20-34+6=0\)

Therefore \(\left(x-2\right)\) is a factor.

Factorise by inspection

\[6{x}^{3}-5{x}^{2}-17x+6=\left(x-2\right)\left(6{x}^{2}+7x-3\right)\]

Factorise fully

\[6{x}^{3}-5{x}^{2}-17x+6 = \left(x-2\right) \left(2x+3\right) \left(3x-1\right)\]

Solve the equation

\begin{align*} 6{x}^{3}-5{x}^{2}-17x+6 & = 0 \\ \left(x-2\right)\left(2x+3\right)\left(3x-1\right) & = 0 \\ x = 2 \text{ or } x & = \frac{1}{3} \text{ or } x = -\frac{3}{2} \end{align*}

Sometimes it is not possible to factorise a quadratic expression using inspection, in which case we use the quadratic formula to fully factorise and solve the cubic equation.

\[x=\frac{-b±\sqrt{{b}^{2}-4ac}}{2a}\]

Worked example 14: Solving cubic equations

Solve for \(x\): \(0 = {x}^{3}-2{x}^{2}-6x+4\)

Use the factor theorem to determine a factor

Let \(f(x)= {x}^{3}-2{x}^{2}-6x+4\)

Try

\(f\left(1\right)={\left(1\right)}^{3}-2{\left(1\right)}^{2}-6\left(1\right)+4=1-2-6+4=-3\)

Therefore \(\left(x-1\right)\) is not a factor.

Try

\(f\left(2\right)={\left(2\right)}^{3}-2{\left(2\right)}^{2}-6\left(2\right)+4=8-8-12+4=-8\)

Therefore \(\left(x-2\right)\) is not a factor.

\(f\left(-2\right)={\left(-2\right)}^{3}-2{\left(-2\right)}^{2}-6\left(-2\right)+4=-8-8+12+4=0\)

Therefore \(\left(x+2\right)\) is a factor.

Factorise by inspection

\[{x}^{3}-2{x}^{2}-6x+4 = \left(x+2\right) \left({x}^{2}-4x+2\right)\]

\({x}^{2}-4x+2\) cannot be factorised any further and we are left with

\(\left(x+2\right)\left({x}^{2}-4x+2\right)=0\)

Solve the equation

\begin{align*} \left(x+2\right)\left({x}^{2}-4x+2\right) & = 0 \\ \left(x+2\right)=0 & \text{ or } \left({x}^{2}-4x+2\right)=0 \end{align*}

Apply the quadratic formula for the second bracket

Always write down the formula first and then substitute the values of \(a,b\) and \(c\).

\[a = 1; \qquad b = -4; \qquad c = 2\]

\begin{align*} x & = \frac{-b±\sqrt{{b}^{2}-4ac}}{2a} \\ & = \frac{-\left(-4\right)±\sqrt{{\left(-4\right)}^{2} -4\left(1\right)\left(2\right)}}{2\left(1\right)} \\ & = \frac{4±\sqrt{8}}{2} \\ & = 2±\sqrt{2} \end{align*}

Final solutions

\(x=-2\) or \(x=2±\sqrt{2}\)

Practise now to improve your marks

You can do it! Let us help you to study smarter to achieve your goals. Siyavula Practice guides you at your own pace when you do questions online.

Sign up to improve your marks

Solving cubic equations

Exercise 5.6

Solve the following cubic equations:

\(x^{3} + x^{2} - 16x = 16\)

\begin{align*} x^{3} + x^{2} - 16x &= 16 \\ x^{3} + x^{2} - 16x - 16 &= 0 \\ \text{Let } a(x) &= x^{3} + x^{2} - 16x - 16 \\ a(-1) &= (-1)^{3} + (-1)^{2} - 16(-1) - 16 \\ &= -1 + 1 +16 - 16 \\ &= 0 \\ \therefore a(x) &= (x + 1)(x^{2} -16) \\ &= (x + 1)(x -4)(x + 4) \\ \therefore 0 &= (x + 1)(x -4)(x + 4) \\ \therefore x=-1 & \text{ or } x = 4 \text{ or } x = -4 \end{align*}

\(-n^{3} - n^{2} + 22n + 40 = 0\)

\begin{align*} n^{3} + n^{2} - 22n - 40 &= 0 \\ \text{Let } a(n) &= n^{3} + n^{2} - 22n - 40 \\ a(-2) &= (-2)^{3} + (-2)^{2} - 22(-2) - 40 \\ &= -8 +4 +44 -40\\ &= 0 \\ \therefore a(n) &= (n + 2)(n^{2} -n -20) \\ &= (n+2)(n-5)(n+4) \\ \therefore 0 &= (n+2)(n-5)(n+4) \\ \therefore n=-2 & \text{ or } n = -4 \text{ or } n = 5 \end{align*}

\(y(y^{2} + 2y) = 19y + 20\)

\begin{align*} y(y^{2} + 2y) &= 19y + 20 \\ y^{3} + 2y^{2} - 19y - 20 &= 0\\ \text{Let } a(y) &= y^{3} + 2y^{2} - 19y - 20 \\ a(-1) &= (-1)^{3} + 2(-1)^{2} - 19(-1) - 20 \\ &= -1 +2 +19 -20 \\ &= 0 \\ \therefore a(y) &= (y + 1)(y^{2} +y -20) \\ &= (y + 1)(y + 5)(y - 4) \\ \therefore 0 &= (y + 1)(y + 5)(y - 4) \\ \therefore y=-1 & \text{ or } y = 4 \text{ or } y = -5 \end{align*}

\(k^{3} + 9k^{2} + 26k + 24 = 0\)

\begin{align*} \text{Let } a(k) &= k^{3} + 9k^{2} + 26k + 24 \\ a(-2) &= (-2)^{3} + 9(-2)^{2} + 26(-2) + 24 \\ &= -8 + 36 - 52 +24 \\ &= 0 \\ \therefore a(k) &= (k + 2)(k^{2} + 7k + 12 ) \\ &= (k + 2)(k+3)(k + 4) \\ \therefore 0 &= (k + 2)(k+3)(k + 4) \\ \therefore k = -2 & \text{ or } k = -3 \text{ or } k = -4 \end{align*}

\(x^{3} + 2x^{2} - 50 = 25x\)

\begin{align*} x^{3} + 2x^{2} - 50 &= 25x \\ x^{3} + 2x^{2} - 25x - 50 &= 0 \\ \text{Let } a(x) &= x^{3} + 2x^{2} - 25x - 50 \\ a(-2) &= (-2)^{3} + 2(-2)^{2} - 25(-2) - 50 \\ &= -8 + 8 + 50 -50 \\ &= 0 \\ \therefore a(x) &= (x + 2)(x^{2} - 25) \\ &= (x + 2)(x-5)(x + 5) \\ \therefore 0 &= (x + 2)(x-5)(x + 5) \\ \therefore x = -2 & \text{ or } x = 5 \text{ or } x = -5 \end{align*}

\(-p^{3} + 19p = 30\)

\begin{align*} -p^{3} + 19p -30 & = 0 \\ p^{3} - 19p + 30 & = 0 \\ \text{Let } a(p) &= p^{3} - 19p + 30 \\ a(3) &= (3)^{3} - 19(3) + 30 \\ &= 27 -57 + 30 \\ &= 0 \\ \therefore a(p) &= (p - 3)(p^{2} + 3p - 10) \\ &= (p-3)(p - 2)(p + 5) \\ \therefore 0 &= (p-3)(p - 2)(p + 5) \\ \therefore p = 3 & \text{ or } p = 2 \text{ or } p = -5 \end{align*}

\(6x^{2} - x^{3} = 5x + 12\)

\begin{align*} 0 = x^{3} - 6x^{2} + 5x + 12 \\ \text{Let } a(x) &= x^{3} - 6x^{2} + 5x + 12 \\ a(-1) &= (-1)^{3} - 6(-1)^{2} + 5(-1) + 12 \\ &= -1 -6 -5 + 12 \\ &= 0 \\ \therefore a(x) &= (x + 1)(x^{2} - 7x + 12) \\ &= (x + 1)(x-3)(x - 4) \\ \therefore 0 &= (x + 1)(x-3)(x - 4) \\ \therefore x = -1 & \text{ or } x = 3 \text{ or } x = 4 \end{align*}